Central venous catheter for hemodialysis: incidence of infection and risk factors - Alessandra Amaral Schwanke; Mitzy Tannia Reichembach Danski; Letícia Pontes; Solena Ziemer Kusma; Jolline Lind
ABSTRACT Objective: To measure the incidence of infection in short-term central venous catheter for hemodialysis and to identify the associated risk factors. Method: Prospective cohort study conducted in a teaching hospital from September 2015 to April 2016. Patients requiring central venous catheter for hemodialysis were included and data was collected through direct and systematic observation of the catheter insertion procedure by the researchers. Results: The final sample consisted of 69 patients, who used 88 catheters. The incidence of infection was 9.1%, and the risk factors were length of hospital stay and insertion of the catheter in the left femoral vein. Conclusion: The observation of the actions performed during the insertion of the catheter made it possible to identify the risk factors associated with infection, and the research protocol may have contributed to the reduction of infection rates.